Pendampingan Pencatatan Kas Harian Berbasis Aplikasi Catatan Keuangan (Buku Kas Harian) Pada UMKM Arabian Kebab Bang Aji Bengkulu - Syahputra, Paldi Awan; Damarsiwi, Eska Prima Monique; Nasution, Suswati; Kresnawati, Kresnawati; Putri, Lydia Gustina; Harwini, Dewi; Tambunan, Denis Ryanto; Yulianti, Oni (Jurnal Dehasen Untuk Negeri, 2025)
MSMEs have an important role in supporting the local economy, but many business actors still face obstacles in financial recording, especially in recording daily cash flow systematically. This community service activity aims to assist UMKM Arabian Kebab Bang Aji Bengkulu in managing daily cash records based on simple financial applications, namely the Daily Cash Book. The implementation method consists of observation, training, direct assistance, and evaluation of the use of the application. The results of the activity show that MSME owners are getting used to using the application to record daily income and expenses, so that they can monitor the financial condition of their business more regularly and accurately. With this assistance, it is hoped that MSMEs can improve financial literacy and make more informed business decisions based on well-documented financial data.